The Translation of Introduction Part of Academy’s Genius Swordmaster’s Comic Using Machine Translation - Arya Nurusy Syifa; Ruminda; Ice Sariyati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study examined the accuracy and clarity of machine translation in the context of fictional texts, with a specific focus on the comic Academy’s Genius Swordmaster. Using Google Translate as the primary tool, a qualitative analysis was conducted to evaluate how effectively the machine translated the comic’s content. The results revealed that 63% of the translated text contained errors, with many issues related to accuracy such as overly literal translations, incorrect word choices, and loss of intended meaning. Problems with clarity were also frequent, as many sentences sounded unnatural, too formal, or awkward in Indonesian, disrupting the flow and making them harder to read. These shortcomings were particularly noticeable in emotional storytelling, where tone, character expression, and cultural nuance play a key role in delivering the intended message. The findings highlight that despite recent advancements, current MT systems still face significant challenges in rendering creative and context-sensitive texts. Future research could expand this work by testing multiple MT systems or exploring post-editing approaches to improve translation quality in fictional narratives.